Schoolteachers and the Nordic Model Comparative and Historical Perspectives - Larsen, Jesper Eckhardt; Schulte, Barbara; Thue, Fredrik W. (Oxford Studies in Comparative Education, 2022)
Schoolteachers and the Nordic Model examines the cultural distinctiveness of the Nordic teaching profession and teacher training compared to examples from Europe and North America. The book explores the concept of these 'teacher cultures' as various dimensions of professional identities, recruitment patterns, teachers' social status, values and knowledge. It considers how Nordic teachers´ socio-cultural backgrounds and their shifting societal roles compare with continental European examples, analysing the societal consequences of teacher cultures for the current Nordic welfare states. Offering a unique focus on teachers, the book uses a shared comparative and historical approach to add new knowledge to the analysis of global convergence and divergence in educational systems. The book will be of great interest to researchers, scholars and post-graduate students in the fields of comparative education, educational policy, the sociology of education and the history of education. It will also be of interest to policy makers, teacher educators and school leaders.